APLIKASI BAHAN ORGANIK AMPAS TEH DAN KOTORAN AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Herlina, Marsa Hany; Sodiq, Abdul Hasyim; Muztahidin, Nur Iman; Firnia, Dewi (Percetakan Umi Toaha Makassar, 2024)
The study aimed to determine the effect of the application of organic matter tea waste and chicken manure on the growth and yield of cayenne pepper plants. The research was carried out from March to May 2024 at Lontar Baru, Kec. Serang-Banten. This study used a Randomized Group Design (RGD) with 2 levels and 3 replications. The first factor was organic matter tea waste with doses of 0 t/ha (equivalent to 0 g/polybag), 2 t/ha (equivalent to 19 g/polybag), 4 t/ha (equivalent to 39 g/polybag), and 6 t/ha (equivalent to 58 g/polybag), while the second factor was organic matter chicken manure with doses of 0 t/ha (equivalent to 0 g/polybag), 8 t/ha (equivalent to 77 g/polybag), and 12 t/ha (equivalent to 115 g/polybag). The results showed that the treatment of tea waste gave the best results in the parameters of the fruit number per plant and the fruit weight per plant. The treatment of chicken manure gave the best results in the parameters of plant height, number of leaves, time of the first flower, fruit number per plant, and fruit weight per plant. There was an interaction between the treatment of organic matter tea waste and chicken manure in the parameters of the fruit number per plant. The treatment of tea waste at 6 t/ha (58 g/polybag) gave the best results in the generative phase of cayenne pepper plants. The treatment of chicken manure at 12 t/ha (115 g/polybag) gave the best results in the growth and yield of cayenne pepper plants.